PENGARUH PEMANFAATAN E-LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA - Myza Uzyla Afryza; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
E-learning is a learning process that leverages technological advancements to facilitate educational activities through online platforms. Within this system, a variety of digital tools and features are provided for both students and lecturers, enabling effective communication, interaction, discussion, and feedback throughout the learning process. These tools—such as discussion forums, virtual classrooms, chat functions, and online assessment features—create an environment that supports active participation and continuous engagement. The availability of such comprehensive facilities not only simplifies the learning process but also enhances comfort, reduces feelings of boredom, and increases students’ overall motivation to learn. The findings of the study demonstrate that e-learning has a substantial and significant impact on students’ learning motivation. This conclusion is supported by the statistical results, where the significance value of 0.000 is below the threshold of 0.05, indicating a meaningful relationship. Additionally, the t-test value of 11.737 exceeds the t-table value of 2.02439, further confirming the significant influence of e-learning on motivation. The R Square value of 77.3% indicates that e-learning contributes strongly to the variance in students’ learning motivation, while the remaining 22.7% is shaped by other external factors not examined in the study. Overall, these results highlight the important role of e-learning in enhancing motivation and improving the quality of learning experiences.